Effect of Brand Association, Service Quality, And Perceived Quality On Customer Loyalty In PT. Surya Eka Kencana Medan: Effect of Brand Association, Service Quality, And Perceived Quality On Customer Loyalty In PT. Surya Eka Kencana Medan - Valencia Valencia; Evelyn Triveda Yawira; Wynda Wynda; Trisyandi Trisyandi; Erwin Erwin (Institute of Computer Science (IOCS), 2020)
The purpose of this study was to examine and analyze the effects of brand association, service quality, and perceived quality on customer loyalty at PT. Surya Eka Kencana Medan both partially and simultaneously. The method used is a quantitative approach to the type of quantitative descriptive research and the nature of the research is descriptive explanatory. The data collection method is done by interview and questionnaire. The data analysis method used is multiple linear regression. The population is customers who rent heavy equipment from PT. Surya Eka Kencana which totaled 127 people in 2019. Sampling used the Slovin formula which produced a sample of 96 people. The results of the study prove that partially brand association (2,608), service quality (3,048), and perceived quality (4, 938) had a positive and significant effect on customer loyalty (1.98609) with a significant level <0.05. Simultaneously brand association, service quality, and perceived quality have a positive and significant effect on customer loyalty, with the results of Fcount (57,549)> Ftable (2.70) significant level <0.05. This research concludes that both partially and simultaneously brand association, service quality, and perceived quality affect customer loyalty at PT Surya Eka Kencana Medan.